2021
DOI: 10.1186/s12912-021-00664-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and psychometric evaluation of the Slovenian version of the nurse professional competence scale

Abstract: Background The competency-based approach to the assessment of nursing practice has been adopted as a key policy in the developed world. The continual self-assessment of competence gives nurses the opportunity to reflect on their competencies and has a significant impact on the quality of nursing practice and patient safety. The study was designed to describe the process of cross-cultural adaptation and to assess the psychometric properties of the Slovenian version of a short form of the Nurse P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
2
19
0
4
Order By: Relevance
“…They accentuated that a dimension of the content structure of professional competence is the 'competency expected in practice', which involves the nurse's professional values of helping, teachingcoaching and work roles. It has also been shown that the different dimensions of nurse professional values-caring, activism, trust, professionalism and justice-are imperative in developing a nurse's professional competence, particularly those focused on clinical care(Prosen et al, 2021).Results also showed the moderate and positive influence of nurse professional values on nurse competence, a finding consistent with previous theoretical assertions. Nursing competency is the nurse's ability to effectively demonstrate attributes including personal characteristics, professional attitude, values, knowledge and skills to fulfil their professional responsibilities(Pueyo-Garrigues et al, 2022) Fukada (2018).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…They accentuated that a dimension of the content structure of professional competence is the 'competency expected in practice', which involves the nurse's professional values of helping, teachingcoaching and work roles. It has also been shown that the different dimensions of nurse professional values-caring, activism, trust, professionalism and justice-are imperative in developing a nurse's professional competence, particularly those focused on clinical care(Prosen et al, 2021).Results also showed the moderate and positive influence of nurse professional values on nurse competence, a finding consistent with previous theoretical assertions. Nursing competency is the nurse's ability to effectively demonstrate attributes including personal characteristics, professional attitude, values, knowledge and skills to fulfil their professional responsibilities(Pueyo-Garrigues et al, 2022) Fukada (2018).…”
supporting
confidence: 83%
“…They accentuated that a dimension of the content structure of professional competence is the ‘competency expected in practice’, which involves the nurse's professional values of helping, teaching‐coaching and work roles. It has also been shown that the different dimensions of nurse professional values— caring, activism, trust, professionalism and justice— are imperative in developing a nurse's professional competence, particularly those focused on clinical care (Prosen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, nursing competence increased continuously in relation to the number of years in the nursing profession, which is also reflected in several international studies. [19,[66][67][68][69][70][71][72][73] The lowest levels of competence in four of the five scale factors were found in the group of newly graduated nurses with less than one year of professional experience. Although competence subsequently increased, the subgroup-specific differences within the first five years of professional experience were not significant in any of the scale factors.…”
Section: Discussionmentioning
confidence: 99%
“…[98] The calculated sample size might basically enable conclusions regarding the general population of RNs working in inpatient general wards, and the characteristics of our sample concerning the distribution of age, gender and experience in the profession adequately reflect the target population. [7] Nevertheless, nurses with formal further qualifications and specializations were overrepresented, [86] which could explain a potential influence on the relatively high ratings [73] on individual items in the total sample, especially as the respective subgroups showed a partly significantly higher competence; the actual ratings in the general population of RNs might hence be lower.…”
Section: Limitationsmentioning
confidence: 99%
“…[32] The NPC Scale Short Form has so far been tested for its psychometric properties in several countries worldwide. The original six-factor structure of the original instrument was confirmed after factor analysis in three studies, [34][35][36] while Prosen et al [37] revealed a fourfactor structure after confirmatory factor analysis and Lee et al [? ] extracted five factors based on principal component analysis.…”
Section: Introductionmentioning
confidence: 99%